The dilemma of COVID-19 vaccination among Health Care Workers (HCWs) of Uttar Pradesh - Singh, Arvind Kumar; Kumari, Rashmi; Singh, Shikhar; Kandpal, Sunil Dutt; Kaushik, Amit (Indian Journal of Community Health, 2021)
Background: Immediately after the outbreak of COVID-19 pandemic, with an unprecedented cooperation between biomedical, pharmaceutical, technological, and political sectors, new vaccines were developed and approved in record times. However, doubts were raised on their efficacy and adverse effects. Globally, it was agreed that the first recipients for vaccines would be the health care workers (HCWs). Logically, it was bound to raise some concerns and result in hesitancy among the HCWs. Aims: The current study was planned to study the proportion of HCWs having hesitancy towards COVID-19 vaccination and factors effecting it. Settings and Design: Cross-sectional study conducted among HCWs of Uttar Pradesh. Methods and Material: The survey was conducted both in online and offline mode and attempted by 254 HCWs eligible for receiving COVID-19 vaccine. Statistical analysis used: t-test, chi-square test, proportion, mean, SD Results: Vaccine hesitancy was present in 35.8% HCWs. Only social factors like caste (p=0.023) and religion (p<0.001) were found to be significantly associated with vaccine hesitancy. Gender, type of health worker, fear of COVID-19 infection, fear of lethality or pre-existing diseases did not affect vaccine hesitancy. The maximum number of HCWs (71.4%) were hesitant because they were unsure of the side-effects followed by the reason of being unsure about its effect on their own health (53.8%). When asked about their attitude towards compulsory COVID-19 vaccination for HCWs, should it be made mandatory by the government, 42.9% were in favour and 40.6% were against any such mandate. Conclusions: The study concluded that social factors like religion and caste are more deterministic for vaccine hesitancy.